2021
DOI: 10.1021/acs.langmuir.1c00684
|View full text |Cite
|
Sign up to set email alerts
|

Few-Layer ZnIn2S4/Laponite Heterostructures: Role of Mg2+ Leaching in Zn Defect Formation

Abstract: Designing nanostructures with extended light absorption via defect engineering is a useful approach for the synthesis of efficient photocatalysts. Herein, ZnIn 2 S 4 was grown hydrothermally in the modified interlayer space of Laponite, resulting in lamellae consisting of Zn-defective ZnIn 2 S 4 several unit cells thick. In the process it was found that Mg 2+ leached from Laponite during synthesis led to the formation of Zn defects in ZnIn 2 S 4 . This resulted in nanohybrids with light absorption extended acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…The morphologies of these PLB samples were anisotropic, elongated, and up to microns in length, whereas BMO synthesized with only CTAB formed square sheets with 50–100 nm edge lengths. This contrasts with syntheses of MoS 2 , In 2 S 3 , and ZnIn 2 S 4 in the pillared Lap interlayer, in which thin semiconductor layers formed a heterolayered structure. Interestingly, CTAB-modified Lap was found to alter the growth orientation of BMO crystals, promoting preferential growth along the [010] direction, which otherwise does not occur in the BMO control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphologies of these PLB samples were anisotropic, elongated, and up to microns in length, whereas BMO synthesized with only CTAB formed square sheets with 50–100 nm edge lengths. This contrasts with syntheses of MoS 2 , In 2 S 3 , and ZnIn 2 S 4 in the pillared Lap interlayer, in which thin semiconductor layers formed a heterolayered structure. Interestingly, CTAB-modified Lap was found to alter the growth orientation of BMO crystals, promoting preferential growth along the [010] direction, which otherwise does not occur in the BMO control.…”
Section: Discussionmentioning
confidence: 99%
“…This results in an expanded interlayer space, the size of which is also dependent on the length of the hydrocarbon tail of the exchanged entity . As a consequence of their high surface area and surface charge, pillared clays have been shown to strongly adsorb dyes and heavy metal cations. , The expanded, organophilic interlayer space in pillared Lap has opened up an avenue for the growth of nanoscopic layered materials in the intergallery space. …”
Section: Introductionmentioning
confidence: 99%
“…Laponite-RD (Lap) is a magnesiosilicate smectite clay of ∼25 nm diameter and 0.92 nm thickness, which can be easily modified due to its high surface area and cation-exchange capacity. In previous studies, surfactant-modified Lap has been shown to be a useful template for colloidal nanoparticle synthesis in both exfoliated and pillared states. The latter tends to lead to the growth of 2D materials with reduced thickness due to the impregnation of the interlayer with nanomaterial precursors. ,, It was also observed that templating the growth of Bi 2 MoO 6 with surfactant-pillared Lap promoted crystal growth along the [010] direction …”
Section: Introductionmentioning
confidence: 99%
“…31−35 The latter tends to lead to the growth of 2D materials with reduced thickness due to the impregnation of the interlayer with nanomaterial precursors. 31,32,34 It was also observed that templating the growth of Bi 2 MoO 6 with surfactant-pillared Lap promoted crystal growth along the [010] direction. 33 The goal of this study is twofold.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous studies have shown that the surfactant-pillared nanoscopic clay Laponite-RD (Lap) can template the growth of a number of semiconductors as thin layers within the Lap intergallery space, strongly influencing both the morphology and the crystalline growth orientation. Interestingly, in the case of Bi 2 MoO 6 (BMO), self-assembly of pillared Lap template particles resulted in micrometer-sized particles with surfaces terminating in predominantly {100}-facets, which were found to be effective at quickly sequestering molecular dyes . In addition, their reuse was achieved by photocatalytic degradation of an aqueous particle dispersion following dye adsorption.…”
Section: Introductionmentioning
confidence: 99%